An Analysis of Chemistry Practical Obstacles in Supporting Deep Learning at SMAN 5 Tangerang Selatan - Nadia Ayu Fania; Buchori Muslim (Universitas Negeri Gorontalo, 2026)
Chemistry laboratory sessions play an important role in supporting deep learning because they provide students with opportunities to construct knowledge through hands-on experiences, reflection, and contextual problem-solving activities. However, despite their importance, the implementation of chemistry laboratory sessions in schools still faces various challenges, and research examining their role in supporting deep learning remains limited. This study aims to analyze the implementation of chemistry practicum and identify the obstacles encountered in supporting deep learning at SMAN 5 Tangerang Selatan. This study employed a quantitative descriptive method using questionnaires, observations, and interviews. The participants consisted of 89 eleventh-grade students and chemistry teachers. The aspects analyzed included laboratory facilities and infrastructure, students’ interest in practicum, practicum implementation time, preparation and implementation of practicum activities, practicum reports, teachers’ ability to explain practicum activities, practicum topics, and the characteristics of deep learning-based practicum modules. The results showed that the overall implementation of chemistry practicum in supporting deep learning was in the good category. The highest percentage was found in the teacher’s ability to explain practicum activities (82.47%). Meanwhile, the lowest percentage was found in laboratory facilities and infrastructure (57.41%). The interview findings revealed that chemistry practicum supported mindful, meaningful, and joyful learning through students’ active participation in experimentation, discussion, and reflection activities. Nevertheless, limited laboratory facilities, low practicum intensity, and insufficiently contextual practicum modules gave significant challenges. These findings suggest the need to improve the laboratory facilities and develop more contextual practicum modules to optimize the implementation of deep learning in chemistry education.